Penerapan Model Supply Chain 4.0 Scorecard di MIKHA Coffee Shop Bandung - Ilham Ramadhani Hasibuan; Rakhmat Ceha; Luthfi Nurwandi (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The purpose of this study was to measure performance of MIKHA Coffee Shop Bandung using Supply Chain 4.0 Scorecard model. The number of samples taken were two experts, which were the owner and manager, five suppliers and 59 consumers of MIKHA Coffee Shop. Data collection was carried out by distributing questionnaires and interviews. The data from the distribution of expert questionnaires was processed using an analytical hierarchy process (AHP) to determine the performance weight values of each hierarchy, meanwhile the data from the distribution of supplier and consumer’s questionnaires determined the rating values. The weight value generated from the analytical hierarchy process (AHP) was multiplied by the rating value to obtain the score. The score value was compiled into a strengths, weaknesses, opportunities and threats (SWOT) analysis diagram to discover the position of each variable, sub-variable and key performance indicator (KPI). The result of the strengths, weaknesses, opportunities and threats (SWOT) analysis diagram based on the level 1 SWOT analysis map was concluded that the financial variable has the highest score and the customer variable obtained the lowest score. The SWOT analysis map level 2 sub-variable customer satisfaction obtained the highest score, meanwhile the infrastructure adequacy for the new technology level obtained the lowest score. The SWOT analysis map level 3 integrated system of KPI obtained the highest score and new information system integration has the lowest score. Abstrak. Tujuan penelitian ini adalah untuk mengukur kinerja di MIKHA Coffee Shop Bandung dengan model Supply Chain 4.0 Scorecard. Jumlah sample yang diambil sebanyak 2 para pakar yaitu owner dan mangaer, 5 supplier dan 59 konsumen MIKHA Coffee Shop, pengumpulan data dilakukan melalui penyebaran kuesioner dan wawancara. Data hasil penyebaran kuesioner pakar diolah menggunakan analitycal hierarchy process (AHP) untuk menentukan nilai bobot kinerja masing-masing hirarki sedangkan data hasil penyebaran kuesioner supplier dan konsumen untuk menentukan nilai rating. Nilai bobot yang dihasilkan dari analitycal hierarchy process (AHP) dikalikan nilai rating untuk mendapatkan nilai skor. Nilai skor selanjutnya dibuatkan diagram analisis strengths weaknesses opportunities and threats (SWOT) untuk mengetahui dimana posisi dari pada masing-masing variabel, sub variabel dan key performance indicator (KPI). Hasil diagram analisis strengths weaknesses opportunities and threats (SWOT) berdasarkan peta analisis SWOT level 1 dapat disimpulkan variabel keuangan memiliki skor tertinggi dan variabel pelanggan dengan skor terendah. Peta analisis SWOT level 2 sub variabel kepuasan pelanggan memiliki skor tertinggi dan kecukupan infrastruktur untuk tingkat teknologi baru memiliki skor terendah. Peta analisis SWOT level 3 KPI sistem yang terintegrasi memiliki skor tertinggi dan integrasi sistem informasi baru memiliki skor terendah. Kata Kunci: Supply Chain 4.0 Scorecard, Kinerja, Rantai Pasok, Supplier, Produsen, Konsumen, AHP, SWOT.